Perception of Fourth Year Medical Students on Task-Based Learning in Clinical Teaching - Shaherzad Sohail, Lubna Raiz Dar (Journal of Rawalpindi Medical College, 2021)
Background Clinical teaching is always challenging. Different teaching strategies are used for effective teaching and learning in a clinical environment. Task-based learning (TBL) is the teaching strategy where tasks are used for the learning of students. We conducted this study to explore student’s perceptions about Task-based learning. Method This descriptive study was carried out for the academic year 2019-2020 in Shalamar medical college Lahore.TBL taught 4th-year MBBS students during a clinical rotation in Gynae/Obs, and at the end of rotation, they were asked to fill a questionnaire regarding their perceptions about TBL. Results 87 students participated in the study. All the students agreed that TBL is an effective teaching approach, and they have a positive response towards TBL in clinical setting.85%students said TBL improve communication skills, 89.6% Said TBL provide the opportunity of direct encounter with patients, 71.2% find it helpful and informative and 40.2%said that it promotes the active involvement of students. Conclusion: Students found TBL as an effective teaching approach in a clinical setting and find it more advantageous because it involves them more in teaching and learning and help them to improve their communication skills, and provide them opportunities to deal with patients.